TOTAL FLAVONOID CONTENT AND ANTIOXIDANT ACTIVITY OF YELLOW PUMPKIN (Cucurbita moschata Duch) FRUIT EXTRACT - Yudha Pratama; Risa Supriningrum; Supomo Supomo (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2024)
Pumpkin (Cucurbita moschata Duch) is a food rich in vitamin A, vitamin C, minerals, carbohydrates, and flavonoid compounds. Flavonoids have several pharmacological activities, including as antioxidants to ward off free radicals. This study aims to determine the total flavonoid content and antioxidant activity of pumpkin fruit. The extraction of pumpkin fruit was done by the maceration method in a 70% ethanol solvent. The total flavonoid test used the colorimetric method with a 10% AlCl3 reagent and quercetin as a positive control. Antioxidant activity was tested using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The results obtained for the total flavonoid content of the ethanol extract of pumpkin fruit amounted to 1.741 mgQE/g ± 0.2438 and an IC50 value of 379.44 ppm, including the category of weak antioxidant, compared with the positive control.